Examining deceptive behaviours by attackers in rugby union: The influence of decoy runners on defensive performance. Issue 6 (December 2018) - Sherwood, Sebastian; Masters, Rich SW; Smith, Tiaki Brett
Background: Deceptive tactics are commonly used in sport; however, the psychological mechanisms underpinning the effectiveness of these tactics are unclear. Increasingly, in rugby union, decoy runners are used to cause deception. Multiple players in an attacking team run option lines off the ball carrier, making it possible that any of the players could receive the ball. Runners who do not receive the ball are decoys. The aim of the tactic is for the decoys to attract attention from defending players, which creates confusion about which player will receive the ball. Aim: To identify behaviours of option line runners that can be used to improve the effectiveness of this deceptive tactic. Method: Observational analysis of completed scrums from the 2015 Super Rugby season (n = 260) during which decoy runners were used by the attacking side. Decoy characteristics, including Hands Up, Line Change and Hands Up with Line Change were noted following each scrum. Gainline success was used as a dependent measure of the efficacy of the decoy characteristics. Characteristics were included in a binary logistic regression analysis to develop a best-fit model for gainline success. Results: Hands Up, Line Change and Hands Up with Line Change significantly improved the likelihood of gainline success seven, eight and six times, respectively. Discussion: We discuss possible mechanisms that underpin the effectiveness of decoy runners and make recommendations for coaches.